Pilot-scale treatment of municipal garbage mechanical dewatering wastewater by an integrated system involving partial nitrification and denitrification. (1st March 2023) - Liao, Runfeng; Song, Zi; Zhang, Jianjun; Xing, Dingyu; Yan, Sibo; Dong, Wenyi; Sun, Feiyun
Abstract: The municipal solid waste (MSW) with high water content can be pre-treated by the mechanical dewatering technology to significantly decrease the leachate generation in sequential landfill treatment or to improve the efficiency for solid waste incineration, which has attracted great concerns recently. However, the generated mechanical dewatering wastewater (MDW) containing high organics and nitrogenous content has been one of the big challenges for the sustainable treatment of MSW. In this study, a pilot-scale integrated system composed of physiochemical pretreatment, anaerobic sequencing batch reactor (ASBR), partial nitrification SBR (PN-SBR), denitrification SBR (DN-SBR), and UV/O3 advanced oxidation process, with a capacity of 1.0 m 3 /d to treat MDW containing over 34000 mg-chemical oxygen demand (COD)/L organics pollutant and 850 mg/L NH4 + -N, was successfully developed. By explorations on the start-up of this integrated system and the process conditions optimization, after a long-term system operation, the findings demonstrated that this integrated system could reach the removal efficiency in the COD, NH4 + -N and total nitrogen (TN) in the MDW of 99.7%, 98.2% and 96.9%, respectively. Partial nitrification and denitrification were successfully obtained for the TN removal with the nitrite accumulation rate of over 80%. The treatment condition parameters were optimized to be 800 mg/L polyaluminum chloride (PAC) and 2 mg/L polyacrylamide (PAM) under a pH of 9 for pretreatment, 36 h hydraulic retention time (HRT) for ASBR, 24 h for PN-SBR, and 2 h for UV/O3 unit. The organic sources in the MDW were also found to be feasible for the DN-SBR. Consequently, the resulting final effluent was stably in compliance with the discharge standard with high stability and reliability. Graphical abstract: Image 1 Highlights: A pilot-scale integrated system was developed for MDW treatment. MDW can be stably treated to satisfy the Chinese discharge standard at an HRT of 36 h. Partial nitrification and denitrification were achieved to remove NH4 + -N in the MDW. Hardly-biodegradable organic substances were mainly removed by the UV/O3 unit.